STRATEGIC SIGNIFICANCE OF RESEARCH UNIVERSITIES IN THE DEVELOPMENT PROSPECTIVE OF HIGHER EDUCATION AND SCIENCE IN THE REPUBLIC OF ARMENIA (Education in the 21st Century, 2023)
Research universities are the key role players in the field of higher education that foster the socio-economic development of the country by significantly contributing to the development of scientific and technological spheres through fundamental research. Research continuously enrich their accumulated experience and scientific knowledge in various fields of activity with new research outcomes, create public good and new strategies of knowledge-based economic development with the aim to ensure that they serve for the needs of science, education, labor market and society. In this context, the strategic significance of establishing research universities in the Republic of Armenia (RA) is highlighted in the current article. In particular, it is substantiated in terms of strengthening the science-education-economy link in the RA, on the one hand, and from the perspective of promoting the development of research and innovation, on the other hand.
Keywords: Keywords: research university, knowledge-based economy, strategic development, higher education, research staff, scientific knowledge.